2018
DOI: 10.1007/s10103-018-2580-z
|View full text |Cite
|
Sign up to set email alerts
|

PBMT and topical diclofenac as single and combined treatment on skeletal muscle injury in diabetic rats: effects on biochemical and functional aspects

Abstract: Physical exercise generates several benefits in a short time in patients with diabetes mellitus. However, it can increase the chances of muscle damage, a serious problem for diabetic patients. Nonsteroidal anti-inflammatory drugs (NSAIDs) are widely used to treat these injuries, despite the serious adverse effects. In this way, photobiomodulation therapy (PBMT) with low-level laser therapy (LLLT) and/or light emitting diode therapy (LEDT) can be used as an alternative in this case. However, its efficacy in tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Experimental animal research (Table 3) supports the beneficial effects of PBM applied before and after exercise in physical activity, through improved performance in endurance training [78,79], decreased level of proinflammatory cytokines [80][81][82][83][84], positive effects on aerobic metabolism [85,86], oxidative stress [86][87][88] and increased ATP [89,90]. Histopathological examination performed after PBM showed that it can protect myonecrosis, reduce pro-inflammatory cell infiltration, muscle destruction, inflammation and can help accelerate tissue repair [91][92][93].…”
Section: Discussionmentioning
confidence: 84%
“…Experimental animal research (Table 3) supports the beneficial effects of PBM applied before and after exercise in physical activity, through improved performance in endurance training [78,79], decreased level of proinflammatory cytokines [80][81][82][83][84], positive effects on aerobic metabolism [85,86], oxidative stress [86][87][88] and increased ATP [89,90]. Histopathological examination performed after PBM showed that it can protect myonecrosis, reduce pro-inflammatory cell infiltration, muscle destruction, inflammation and can help accelerate tissue repair [91][92][93].…”
Section: Discussionmentioning
confidence: 84%
“…Changes in ankle angle and calcaneus height have been shown in contusion models of anterior tibialis muscle injury (20), suggesting impaired joint rotation/movement. Additionally, voluntary walking impairment has previously been shown (19) in a rat model of traumatic muscle injury. In this study, treadmill-based walking trials were performed in triplicate to assess reproducibility in our clinical assessments.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, the controlled study of MTJ injury progression in a clinically relevant pre-clinical model may allow for the development of novel therapeutics and treatment strategies for patients who suffer from such injuries. Animal models of muscle injury include chemical (15), traumatic (16,17), acute high intensity exercise (18), contusion (19)(20)(21), contraction (22), and ischemia-reperfusion (23) methods (for a summary of published models see appendix 1). While valuable, the majority of current models do not specifi-cally target the MTJ, a common site of clinical strain-induced activity-related injuries (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…15,32 The reduction of the level of pain-related molecules such as prostaglandin E2 and cyclooxygenase-2 has also been documented. 33 As we well know, the postoperative pain of individuals submitted to tonsillectomy lasts about 14 days, delaying the return to daily activities and to a normal diet, with the risk of dehydration. 27 In severe cases, postoperative pain may result in delayed discharge, emergency department visits, or readmission to the hospital for pain control and hydration.…”
Section: Discussionmentioning
confidence: 99%